Engaging isatins in solvent-free, sterically congested passerini reaction - Kaicharla, Trinadh; Yetra, Santhivardhana Reddy; Roy, Tony; Biju, Akkattu T. (Green Chemistry, 2013)
A facile, atom-economic and environmentally-benign protocol for the synthesis of biologically important oxindole derivatives in high yields has been demonstrated by employing isatins as carbonyl compound surrogates in a Passerini reaction carried out under solvent-free conditions. Moreover, electron-deficient phenols can also be used as the acid component in this reaction. In addition, the synthetic utility of the present methodology was examined by the one-pot synthesis of oxindoles with a free -OH group at the benzylic position.

Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and isatins - Bhunia, Anup; Roy, Tony; Pachfule, Pradip; Rajamohanan, Pattuparambil R.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2013)
Mix and match: With isoquinoline as the nucleophilic trigger, multicomponent reactions afforded spirooxazino isoquinoline derivatives, proceeding through 1,4-dipolar intermediates. The use of pyridine as a nucleophile furnished indolin-2-one derivatives, with the reaction likely proceeding through a pyridylidene intermediate.

Rapid access to benzoxaphospholes and their spiro analogues by a three-component coupling involving arynes, phosphines, and activated ketones - Bhunia, Anup; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
An operationally simple multicomponent coupling involving in situ generated arynes from 2 (trimethylsilyl)aryl triflates, phosphines, and various acyclic and cyclic activated carbonyl compounds has been developed. The reaction proceeds via a formal [3 + 2] cycloaddition mode giving access to differently substituted (spiro)benzoxaphosphole derivatives in moderate to good yields Mild reaction conditions. a broad scope. and the possibility of varying all the three-components are the notable features of the present reaction.

Synthesis of functionalized coumarins and quinolinones by NHC-catalyzed annulation of modified enals with heterocyclic C-H acids - Yetra, Santhivardhana Reddy; Roy, Tony; Bhunia, Anup; Porwal, Digvijay; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
N-Heterocyclic carbene (NHC) catalyzed lactonization and lactamization of 2-bromoenals with heterocyclic C–H acids proceeding via the α,β-unsaturated acyl azolium intermediates is reported. The reaction furnished coumarin- or quinolinone-fused lactone/lactam derivatives. In addition, results of the enantioselective version of this reaction using chiral NHC are presented.

Synthesis of N-aryl beta-amino alcohols by trifluoroacetic acid promoted multicomponent coupling of aziridines, arynes, and water - Roy, Tony; Baviskar, Dnyaneshwar R.; Biju, Akkattu T. (Journal of Organic Chemistry, 2015)
A transition-metal-free, three-component coupling involving N-substituted aziridines, arynes, and water promoted by trifluoroacetic acid (TFA) has been reported. The reaction furnished medicinally important N-aryl beta-amino alcohol derivatives in moderate to good yields. In addition, the use of azetidines in this reaction afforded N-aryl gamma-amino alcohol derivatives.

Aryne [2,3] stevens rearrangement - Roy, Tony; Thangaraj, Manikandan; Kaicharla, Trinadh; Kamath, Rupa V.; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
Arynes are employed in the transition-metal-free and mild [2,3] Stevens rearrangement of tertiary allylic amines for the synthesis of functionalized homoallylic amines in moderate to good yield with a broad substrate scope. The key nitrogen ylide intermediate was generated by the N-arylation of allyl amines using arynes. Moreover, the reaction of chiral allyl amines with arynes resulted in the enantiospecific synthesis of homoallylic amines. In addition, preliminary studies on the [1,2] Stevens rearrangement is also presented.

Employing carboxylic acids in aryne multicomponent coupling triggered by aziridines/azetidines - Roy, Tony; Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Thangaraj, Manikandan; Garai, Bikash; Biju, Akkattu T. (Organic Chemistry Frontiers, 2016)
The transition-metal-free aryne multicomponent coupling (MCC) involving carboxylic acids initiated by aziridines/azetidines has been reported. The use of aziridines as nucleophiles afforded N-aryl beta-amino alcohol derivatives and the application of azetidines as nucleophilic triggers furnished N-aryl gamma-amino alcohol derivatives in moderate to good yields. These reactions proceed under mild conditions and result in the formation of a new carbon-nitrogen bond and a new carbon-oxygen bond. The utility of carboxylic acids in aryne MCCs has been demonstrated, and the synthetic potential of phenols as acid surrogates in the present aryne MCCs has been realized.

Lewis acid catalyzed selective reactions of donor-acceptor cyclopropanes with 2-naphthols - Kaicharla, Trinadh; Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
Lewis acid-catalyzed reactions of 2-substituted cyclopropane 1,1-dicarboxylates with 2-naphthols is reported. The reaction exhibits tunable selectivity depending on the nature of Lewis acid employed and proceed as a dearomatization/rearomatization sequence. With Bi(OTf)(3) as the Lewis acid, a highly selective dehydrative [3+2] cyclopentannulation takes place leading to the formation of naphthalene-fused cyclopentanes. Interestingly, engaging Sc(OTf)(3) as the Lewis acid, a Friedel-Crafts-type addition of 2-naphthols to cyclo-propanes takes place, thus affording functionalized 2-naphthols. Both reactions furnished the target products in high regioselectivity and moderate to high yields.
Keywords: annulations; arenes; Lewis acids; reaction mechanisms; small ring systems

Substrate-controlled selectivity switch in the three-component coupling involving arynes, aromatic tertiary amines, and CO2 - Bhojgude, Sachin Suresh; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2016)
The transition-metal-free multicomponent coupling involving arynes, aromatic tertiary amines, and CO2 is reported. The reaction exhibits switchable selectivity depending on the electronic nature of the aromatic amines used. With amines bearing electron-releasing/neutral groups as the nucleophilic trigger, the reaction afforded 2-arylamino benzoates via a nitrogen to oxygen alkyl group migration. Employing electron-deficient amines in the reaction furnished 2-aminoaryl benzoates proceeding via the aryl to aryl amino group migration resembling a Smiles rearrangement.

Synthesis of functionalized amino epoxides by a three-component coupling involving aziridines, arynes and aldehydes - Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2016)
A transition-metal-free three-component coupling involving N-substituted aziridines, arynes and aldehydes resulting in the formation of trisubstituted N-aryl alpha-amino epoxides has been demonstrated. The reaction likely proceeds via the highly strained cyclic nitrogen ylide intermediates generated from aziridines and arynes.

Metal-free, brønsted acid-catalyzed formal [3+2] annulation of quinone monoacetals with 2-naphthols - Jacob, Anu; Roy, Tony; Kaicharla, Trinadh; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
An operationally simple and metal-free cross-coupling of quinone monoacetals (QMAs) with 2-naphthols catalyzed by triflic acid is reported. This formal [3+2] annulation allowed the synthesis of diverse naphtho[2,1-b]benzofuranderivatives in moderate to good yields. Preliminary mechanistic studies reveal the initial nucleophilic substitution of QMAs with 2-naphthols in preference to the mixed acetal formation and subsequent [3,3] sigmatropic rearrangement.

Synthesis of functionalized β-keto arylthioethers by the aryne induced [2,3] Stevens rearrangement of allylthioethers - Thangaraj, Manikandan; Gaykar, Rahul N.; Roy, Tony; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
A mild and transition-metal-free synthesis of β-keto arylthioethers has been developed by the aryne triggered [2,3] Stevens rearrangement of allylthioethers. The key sulfur ylide intermediate for the rearrangement was formed by the S-arylation of allylthioethers with arynes generated from 2-(trimethylsilyl)aryl triflates using CsF. Later, the reaction products are converted into valuable heterocycles in two steps.

Recent advances in molecular rearrangements involving aryne intermediates - Roy, Tony; Biju, Akkattu T. (Chemical Communications, 2018)
This Feature Article is aimed at highlighting the recent developments in the transition-metal-free molecular rearrangements involving arynes. The chemistry of arynes has shown incredible developments especially in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions in the last three decades. The rapid growth in this field is mainly due to the development of mild methods for the generation of arynes. One aspect of the recent developments in the chemistry of arynes involves the molecular rearrangements proceeding via this electrophilic intermediate. The molecular rearrangements have provided direct access to a library of valuable molecules, which cannot be accessed in a single step through other synthetic routes. Herein, we present a concise account on the developments that occurred in this field over the last three decades.

[8+3]-cycloaddition of tropones with azaoxyallyl cations - Roy, Tony; Jacob, Anu; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemistry-An Asian Journal, 2019)
Although azaoxyallyl cations are widely used as 1,3-dipoles for various cycloaddition reactions leading to nitrogen-containing heterocycles, their application in higher-order cycloaddition reaction remains scarce. Herein, we present the [8+3]-cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one-step construction of cycloheptatriene-fused 1,4-oxazinones in moderate to good yields. This base-promoted new carbon-oxygen and carbon-nitrogen bond-forming reaction takes place under mild conditions in the absence of transition metal catalysts.
Keywords: 1; 4-oxazinones; azaoxyallyl cations; heterocycles; tropones; [8+3] cycloaddition

Aryne Sommelet-Hauser rearrangement - Roy, Tony; Gaykar, Rahul N.; Bhattacharjee, Subrata; Biju, Akkattu T. (Chemical Communications, 2019)
An aryne induced transition-metal-free and mild Sommelet-Hauser rearrangement of tertiary benzylamines for the synthesis of -aryl amino acid derivatives in moderate to good yields is presented. Unlike the conventional Sommelet-Hauser rearrangement of ammonium salts, the methodology developed herein requires neither harsh conditions nor strong bases. Moreover, a temperature dependent switchable selectivity for the Sommelet-Hauser and Stevens [1,2] rearrangements has been observed.

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions